Screening of Trichoderma spp. against Rhizoctonia solani the causal agent of rice sheath blight - A.P. SINHA, ASHRAF ALl KHAN* and (Indian Phytopathology, 2007)
Observations on the radial growth of different isolates of Trichoderma spp. showed that Trichoderma harzianum was the fastest growing fungus is followed by T. virens and Trichoderma sp. (Isolate 107).After 144 hr of co-culture with Rhizoctonia solani, T. harzianum and T. virens attained a growth of 90 mm and 89 mm, respectively. While Trichoderma sp. (Isolate 87) attained a growth of 83.2 mm which is significantly inferior to the growth attained by T. harzianum and T. virens. Volatile compounds produced by T. harzianum resulted in maximum inhibition (59.7%)of mycelial growth of R. solani after 48 hr. The culture filtrate of T. harzianum and T. virens used at 50 percent concentration showed 76.3 percent and 70 percent inhibition, respectively in the mycelial growth of test pathogen. All the isolates of Trichoderma spp. Significantly reduced severity and incidence of rice sheath blight. T. harzianum was most effective showing 38.8percent and 24.6 percent reduction in disease severity and incidence. The highest increase in grain yield/plant (21.0%) and 1000-grain weight (6.3%) were obtained with T. harzianum. Of the five isolates of Trichoderma spp. screened under in vitro and glass house conditions, T. harzianum (rice leaf sheath isolate) was found most effective against R. solani.